Simulation and implementation of UWB filter structures - Bonifacio, Marvin T. (2009)
Ultra-wideband (UWB) bandpass filters are key passive components in keeping the spectrum of the UWB signals to meet the FCC's spectrum mask. In this undergraduate student project, novel designs of various BPF's for UWB applications were implemented. The filter designs were obtained from the IEEE papers surveyed. Focus was put on structural designs and implementations using Optimum Stubs. Microwave Studio from Computer Simulation Technology (CST) was used to simulate the filter structures. Theoretical results obtained from the papers were verified in simulations ran. The simulation results were compared using the following criteria: bandwidth, insertion loss, group delay and out-band performance. Two filters, one without a notch band and one with a notch band, with the optimal performance were fabricated on FR4 boards for actual verification.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Ultra-wideband devices; Microwave circuits -- Testing; Microwave filters; Electric filters